Photocatalyic Appel reaction enabled by copper-based complexes in continuous flow - Minozzi, Clémentine; Grenier-Petel, Jean-Christophe; Parisien-Collette, Shawn; Collins, Shawn K. (Beilstein Journal of Organic Chemistry, 2018)
A copper-based photocatalyst, Cu(tmp)(BINAP)BF4, was found to be active in a photoredox Appel-type conversion of alcohols to bromides. The catalyst was identified from a screening of 50 complexes and promoted the transformation of primary and secondary alcohols to their corresponding bromides and carboxylic acids to their anhydrides. The protocol was also amendable and optimized under continuous flow conditions.
Keywords: Appel; continuous flow; copper; halides; photocatalysis